Calcium regulates processing of the Alzheimer amyloid protein precursor in a protein kinase C-independent manner. - Buxbaum, J D (1994)
Various first messengers linked to phospholipase C, including acetylcholine and interleukin 1, regulate the production both of the secreted form of the amyloid protein precursor (APP) and of amyloid beta-protein. We have now identified intracellular signals which are responsible for mediating these effects. We show that activation of phospholipase C may affect APP processing by either of two pathways, one involving an increase in protein kinase C and the other an increase in cytoplasmic calcium levels. The effects of calcium on APP processing appear to be independent of protein kinase C activation. The observed effects of calcium on APP processing may be of therapeutic utility.